Positive Data Visualization Using Trigonometric Function - Farheen Ibraheem; Maria Hussain; Malik Zawwar Hussain; Akhlaq Ahmad Bhatti (Journal of Applied Mathematics)
A piecewise rational trigonometric cubic function with four shape parameters has been constructed to address the problem of visualizing positive data. Simple data-dependent constraints on shape parameters are derived to preserve positivity and assure smoothness. The method is then extended to positive surface data by rational trigonometric bicubic function. The order of approximation of developed interpolant is .